The Origins of Archaeological Heritage Protection in Lithuania - Kuncevičius, Albinas; Poškienė, Justina (Archaeologia Lituana, 2017)
The processes of legislation and the development of systems for the preservation of ancient remains, including archaeological heritage, were under development in the countries of Western Europe during the 19th century. The paper seeks to observe the ideas and practices of heritage preservation in Lithuania under the Russian Empire – it is intended to reveal the circumstances under which the notion of heritage protection was born and the ways of its practical implementation. The origins of archaeological science and heritage protection in Lithuania can be traced to the beginning of the 19th c. By the middle of the century, elements of professional heritage protection were implemented in the activities of the Vilnius Museum of Antiquities and the Vilnius Temporary Archaeological Commission. Certain components of professional heritage protection were established in the end of the 19th c.; nevertheless, attempts to pass the general law and to introduce the system of archaeological heritage protection in the Russian Empire were not successful. The birth of a modern Lithuanian nation demanded relevant approaches toward its past in late 19th–early 20th centuries. Efforts were put into the development of the modern Lithuanian national state thus delaying the development of a professional heritage protection system. Keywords: archaeology, science, heritage protection, history of archaeology